Effects of dietary n‐3 to n‐6 fatty acid ratios on spawning performance and larval quality in tongue sole Cynoglossus semilaevis. (14th August 2013) - Liang, M.‐Q.; Lu, Q.‐K.; Qian, C.; Zheng, K.‐K.; Wang, X.‐X.
Abstract This study investigated the effect of n‐3 to n‐6 fatty acid ratios in broodstock diets on reproduction performance, fatty acid composition of eggs and gonads of tongue sole Cynoglossus semilaevis. Broodstock were fed five isonitrogenous and isoenergetic diets for 60 days. The supplemented lipids were prepared by a combination of fish oil and soybean oil inclusion FO (fish oil); FSO1 (fish oil: soybean oil = 7:1); FSO2 (fish oil: soybean oil = 2.2:1); FSO3 (fish oil: soybean oil = 1:1); FSO4 (fish oil: soybean oil = 1:4.3) as lipid sources with different n‐3 to n‐6 fatty acid ratios 10.40, 5.21, 2.81, 1.71 and 0.87. Results showed that relative fecundity, fertilization rate and survival rate of larvae at 7 days posthatching were all higher in broodstock fed FSO1 and FSO2 diet and significantly (P < 0.05) decreased in groups fed FSO3 and FSO4 diets. The best result in starvation tolerance test was obtained in FSO2 diet. The present study suggests that n‐3 and n‐6 PUFA ratio in broodstock diet has a considerable effect on spawning performance, egg and larval quality for C. semilaevis.